Nitrogen and carbon metabolism evaluation in paricá plants subjected to different cadmium concentrations (Bioscience Journal, 2022)
The development of anthropogenic activities such as industry, mining, agriculture, urban waste discard has been, the main actions that result in increased contamination by heavy metals in soil, water and air. One of the most harmful metals made available by these activities is cadmium, and even at low concentrations it is very toxic mainly in plant structures. The objective of this work was to verify the biochemical behavior of nitrogen and carbon metabolism in young plants of paricá when submitted to increasing cadmium application. For this, a completely randomized experiment was carried out with five treatments (control, CdCl2 178 μM, CdCl2 356 μM, CdCl2 534 μM, CdCl2 712 μM), with seven replicates, totaling 35 experimental units. The sensitivity of this vegetable to the increasing concentrations of cadmium was evident. The root system it presents’’ saw where the most toxic element accumulated, solutes such as carbohydrates, sucrose were affected in their concentrations, mainly in the leaves. The root system saw in its concentrations of glycine betaine a possibility of osmoprotection, but this did not reflect an increase in the concentration of nitrate in both leaf and roots. In the other hand, this fact not observed by the concentration of ammonium that increased in the root system. The results showed that the cadmium was transported to aerial part, however, concentrated mainly in the root system characterizing as a phytoextractor species.